Charting just futures for Aotearoa New Zealand: philosophy for and beyond the Covid-19 pandemic - Mulgan T; Enright S; Grix M; Jayasuriya U; Ka‘ili TO; Lear AM; Māhina ANM; Māhina Ō; Matthewson J; Moore A; Parke EC; Schouten V; et al. (Taylor and Francis Group, 2021)
The global pandemic needs to mark a turning point for the peoples of Aotearoa New Zealand. How can we make sure that our culturally diverse nation charts an equitable and sustainable path through and beyond this new world? In a less affluent future, how can we ensure that all New Zealanders have fair access to opportunities? One challenge is to preserve the sense of common purpose so critical to protecting each other in the face of Covid-19. How can we centre what we have learnt about resilience within Māori and wider Pacific communities in our reforms? How can public understanding of Covid-19 science create a platform for the future social valuing of expertise? How can we ensure that the impact of Covid-19 in New Zealand results in a more sustainable, and inclusive workforce – for instance by expanding our perceptions of the value of our workers through promoting digital inclusion? To meet these challenges, we must reimagine our existing traditions of thought, breathing new life into perennial concepts and debates. Our paper indicates some of the ways that Philosophy is central to this collective reimagining, highlighting solutions to be found across our rich philosophical traditions.
Keywords: Philosophy; just futures; intergenerational well-being; ethics; resilience